The Next Frontier of Outcomes Research: Collaborative Quality Initiatives. Issue 5 (May 2020) - Billig, Jessica I.; Kotsis, Sandra V.; Chung, Kevin C.
Abstract : Summary: Quality improvement efforts at the federal level have instituted both rewards and penalties as incentives to improve health care quality. However, neither of these methods has shown long-lasting improvements. Furthermore, many programs have focused on decreasing mortality or hospital readmissions, measurements that are not applicable to many surgical fields, including plastic surgery. One model that has been shown to be effective is a collaborative quality initiative that uses a pay-for-participation method whereby participants learn from one another and institute changes to improve patient care. Many of these changes are process measures that are easier to implement and quicker to show improvement than structural or outcome measures. Regional collaborative quality initiatives have been developed in other surgical specialties such as bariatric surgery and urology. Currently, the authors are establishing a new collaborative quality initiative for hand surgery: the Michigan Collaborative Hand Initiative for Quality in Surgery. It is a collaboration of nine sites with the goal of identifying areas that are in need of quality improvement in hand surgery and implementing measures to improve on them. The authors believe that collaborative quality initiatives will promote high-quality care and should be incorporated into the field of plastic surgery.